Who said hip-hop was dead? The politics of hip-hop culture in Immortal Technique's lyrics. (July 2015) - Vito, Christopher
While much of mainstream hip-hop has been corporatized and commercialized by major corporations, strands of independent hip-hop have attempted to remain separated from the major record labels. Using hermeneutic methods, this article examines the lyrics of independent hip-hop artist Immortal Technique. This article identifies three central themes in Immortal Technique's lyrics that illustrate how he expresses resistance to class domination. First, he argues that class conflict occurs in hip-hop and thus there needs to be a pull away from major corporations. Second, his lyrics point for the need for independent hip-hop to escape from false consciousness and resist hegemony. Finally, his work indicates that the creation of knowledge through independent hip-hop culture and language present a means to resist class domination.